2006
DOI: 10.1016/j.juro.2006.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nicotinamide N-Methyltransferase as a Novel Tumor Marker for Renal Clear Cell Carcinoma

Abstract: Our results indicate that a marked nicotinamide N-methyltransferase increase is a peculiar feature of clear cell renal cell carcinoma. Additional studies may establish the role of nicotinamide N-methyltransferase in tumor formation and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 20 publications
8
80
0
Order By: Relevance
“…Recent studies have demonstrated that NNMT is aberrantly expressed in a number of tumors, suggesting that NNMT serves an important function in tumor development (12,13). Additionally, the serum levels of NNMT were significantly increased in patients with colorectal, lung and renal cell carcinoma compared with those in the control group (10,14,15). Previous studies have also demonstrated that the upregulation of NNMT is associated with poor prognosis, advanced tumor stage, tumor cell migration and invasion (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that NNMT is aberrantly expressed in a number of tumors, suggesting that NNMT serves an important function in tumor development (12,13). Additionally, the serum levels of NNMT were significantly increased in patients with colorectal, lung and renal cell carcinoma compared with those in the control group (10,14,15). Previous studies have also demonstrated that the upregulation of NNMT is associated with poor prognosis, advanced tumor stage, tumor cell migration and invasion (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In renal cell carcinoma NNMT mRNA was overexpressed in 100% of clear cell renal cell carcinomas (ccRCCs) compared to adjacent noncancerous tissue. Moreover, NNMT expression level in ccRCC showed an inverse correlation with tumor size, suggesting a role of the enzyme in tumour growth (3). In oral squamous cell carcinoma NNMT upregulation inversely correlated with pT, pathological staging and lymph node metastasis (4).…”
mentioning
confidence: 99%
“…Interestingly, many cancers have been reported to have an enhanced expression of NNMT. [22][23][24][25] As NNMT activity is positively related to nicotinamide levels, as demonstrated by Riederer et al, 20 it is likely that elevated NNMT expression in cancers may therefore be related to excessive niacin intake.…”
Section: Discussionmentioning
confidence: 92%